EFL Students' Perceptions of the Online Undergraduate Thesis Supervision Process - Nunung Sari Sandria (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of the study to know how student perceptions of the online thesis supervision process for students majoring in English Education at the University of Islam Malang. To achieve the above objectives, researchers conducted a type of qualitative descriptive research. Data collection procedures were carried out using questionnaires and interviews. To obtain student perception questionnaire data, the questionnaire was given to all students online using Google Forms. After the participants filled out all the questionnaires, the researcher interviewed four selected students with two interviews and the duration of the interview was 30 minutes with the aim of exploring their perceptions of online thesis supervision. In the data analysis section, the researcher analyzed the data results using quantitative and qualitative techniques. For quantitative data, the researcher used a student perception questionnaire from Mushoriwa (2014). Student perceptions consist of two types of expressions, namely positive and negative. Periodic handling of qualitative data is carried out based on the comprehensive analysis method by Miles and Huberman (1994). It contains three parallel streams: data reduction, data display, and conclusion. In this study, students' perceptions of online thesis guidance said that students' perceptions were more dominant towards positive perceptions such as supervisors providing useful input and helping students in advancing their thesis so that they were able to complete it faster and be more focused when compiling a thesis. Things that need to be considered as suggestions are how in the future to add samples in data collection such as adding lecturers as participants so that it is clearer from student perceptions and lecturers' perceptions.Key words: EFL Students’, Online Thesis Supervision, Perceptions, Undergraduate